50th Anniversary of the Cuban Journal of Dentistry - Josefa Dolores Miranda Tarragó; Luisa Haydeé Alfonso Dreke (Editorial Ciencias Médicas, 2014)
The first issue of the Cuban Journal of Stomatology was published on June 30, 1964, although the first article related to this discipline in Cuba appeared in the Diario de La Habana, the 1st. March 1829 In 1868 the Surgical and Dentistry Medical Journal was founded, followed by several short journals and different names, always related to stomatology and the intention to disseminate the scientific advances of the profession. The Cuban Journal of Stomatology, sponsored by the Cuban Society of Stomatology, maintains its operation to date with the mission of contributing to the dissemination of scientific research of Cuban stomatology and the rest of the world. It is indexed in WoK (SciELO Citation Index) since January 2001, SCOPUS, Ulrich's, LILACS, Latin American Index, Cubaciencias, SciELO, Latindex and CUMED. It is certified by CITMA since 2007. It uses Open Journal Systems 2.3.8.0, free management software and publication of journals developed, supported, and freely distributed by the Public Knowledge Project under GNU General Public License with the principle that the free availability of the Research helps greater exchange and global knowledge. The journal has been published in digital format since 1996 and on an online platform since 2012. It accepts for evaluation original research articles, systemic reviews, presentations or case reports, as well as any other variant of scientific communication, with prior approval of the editorial committee. Receive contributions in Spanish, English and Portuguese. At present, the need to study the visibility of scientific publications and articles has increased, which conditions their subsequent impact. The number of scientific articles published is a useful indicator to measure the progress of the different spheres of science and technology in a country; above all, when it is based on the study of large international databases, which treasure the publications that its producers consider to be the most important in their respective thematic areas. Other scientists think that it is more interesting to know the impact of the authors than that of the articles, and there are authors who consider the factor of inappropriate and indiscriminate impact. However, universities, regions and countries remain interested in exploring what their visibility is. To achieve greater scientific visibility, the articles must have high quality, with very rigorous selection and evaluation processes. Cuba has the strength of having stomatologists of high scientific level and that has to be reflected in its publications. Fifty years after the publication of the Cuban Magazine of Stomatology, our main responsibility is to continue raising the demand and quality to achieve greater visibility and that in its pages the achievements of the Cuban stomatology are reflected, as well as the advances of other countries that want to publish in our magazine.